2012
DOI: 10.2174/138945012802009053
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene C4 Synthase: Upcoming Drug Target For Inflammation

Abstract: Leukotrienes are important mediators of pain and inflammation and they are produced in the arachidonic acid pathway via 5-lipoxygenase. They have been shown to have important roles in pyresis following antigen attack and in aspirin- intolerant asthma. They promote inflammation processes including eosinophil migration, increase in vascular permeability and bronchoconstriction. Hence, targeting the enzymes involved in the synthesis of these mediators can lead to the development of novel anti-inflammatory drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Histamine and leukotrienes, two main targets of most commercial anti-allergy treatments, are some of the many molecules released by both mast cells and basophils. Histamine and leukotrienes have immediate effects like increasing vascular permeability and bronchoconstriction [29,30] and long-term effects mediated by regulation of other inflammatory cells, including eosinophil recruitment and adhesion and Th2 promoting DCs [31,32]. The ability of basophils to independently recruit eosinophils and neutrophils in chronic allergic inflammation was demonstrated in a mouse model, and the low abundance (<2%) of basophils in the infiltrates suggested that basophils initiate rather than effect chronic inflammation [33].…”
Section: Role Of Il-18 In Allergic Diseasementioning
confidence: 99%
“…Histamine and leukotrienes, two main targets of most commercial anti-allergy treatments, are some of the many molecules released by both mast cells and basophils. Histamine and leukotrienes have immediate effects like increasing vascular permeability and bronchoconstriction [29,30] and long-term effects mediated by regulation of other inflammatory cells, including eosinophil recruitment and adhesion and Th2 promoting DCs [31,32]. The ability of basophils to independently recruit eosinophils and neutrophils in chronic allergic inflammation was demonstrated in a mouse model, and the low abundance (<2%) of basophils in the infiltrates suggested that basophils initiate rather than effect chronic inflammation [33].…”
Section: Role Of Il-18 In Allergic Diseasementioning
confidence: 99%
“…Cysteinyl leukotrienes have been shown to have important roles in asthma. They promote inflammation processes including eosinophil migration, increase in vascular permeability and bronchoconstriction (Devi et al, 2012). In this study the most common allergens causing positive skin test among asthmatic patients were pollen (63.41%), smoke (53.65%), hay dust (48.78%) and house dust (40%).…”
Section: Discussionmentioning
confidence: 69%
“…LTC4S inhibitors are lukast alternatives with resolutionpromoting properties. In spite of its central role in allergic in flammation, very few specific inhibitors of LTC4S have been developed thus far (143)(144)(145). This may reflect the success of CysLT1 antagonists, collectively referred to as "lukasts," that are currently used in clinical management of asthma.…”
Section: Therapeutic and Pharmacological Opportunities And Pitfallsmentioning
confidence: 99%